The new constitution freezing the press: Freedom of expression and statutory limitations in Libya - Miral Sabry Alashry (Taylor & Francis Group, 2021)
This study examined the Libyan conflict which started in 2011 until now. In the same way, the study also focused on how Libyan journalists are fighting for media freedom, particularly in the context of the media laws in the new Constitution of 2017. Through focus group discussions were done with 40 Libyan journalists. The findings of the study indicated that some media laws did not conform to the international laws and UN treaties, which the Libyan Parliament Committee approved. Another finding of the study was that the journalists advocated for a change in the media laws so that they subscribe to the international law. In addition, the journalists also noted that the Constitution should guarantee press freedom. The journalists indicated that they receive threats if they publish stories critical of the governments or ISIS. They also suggested that their actions as journalists have not been sufficiently factored into the political science framework of the safety valve which may be playing the same role with the new democratisation process in 2021. In the context of these findings, the following recommendations were made: the new government should change Articles 35, 37, 38, 42, 43, 46 and 132 to conform to the international laws and UN treaties.